2017
DOI: 10.1097/ruq.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Ultrasound-Guided Knee Injection Through a Lateral Suprapatellar Approach

Abstract: Our study demonstrates that in-plane ultrasound-guided injection of the knee in semiflexion approaching the lateral suprapatellar recess is a safe and useful technique to administer intra-articular contrast solution, as an alternative method without radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…A variety of ultrasound guided and anatomically guided knee injection techniques have been described in the literature. 7,[17][18][19] These approaches use various combinations of ultrasound and anatomical landmarks to access the intra-articular space. One of the most common ultrasound guided methods accesses the joint space through the suprapatellar bursa and its anatomical connection to the intrarticular space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of ultrasound guided and anatomically guided knee injection techniques have been described in the literature. 7,[17][18][19] These approaches use various combinations of ultrasound and anatomical landmarks to access the intra-articular space. One of the most common ultrasound guided methods accesses the joint space through the suprapatellar bursa and its anatomical connection to the intrarticular space.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common ultrasound guided methods accesses the joint space through the suprapatellar bursa and its anatomical connection to the intrarticular space. 17 Another common method uses anatomical guidance, where the needle is inserted lateral to the patella tendon of the flexed knee and directed medially until it encounters the hard end point of the medial femoral condyle. In this approach location in the joint space is supported by the positioning of the needle at point of entry and timing of the hard stop.…”
Section: Discussionmentioning
confidence: 99%
“…Chagas-Neto FA et al [20] showed that in-plane ultrasound-guided injection of the knee in semiflexion approaching the lateral supra-patellar recess is a safe and useful technique administers intra-articular contrast solution, as an alternative method without radiation exposure. Park Y et al [34] showed that accuracy of ultrasound-guided supra-patellar bursal injection was more than blind approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Curtis HM and Park Y [35] demonstrated that suprapatellar approach was safer than other approach for intra-articular injection. Such technique permits to control the needle throughout the entire procedure from the puncture site to the articular cavity, avoiding vital structures such as tendons and cartilage [20]. In our study, we performed this technique to increase the accuracy in order to compare two methods of approaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation